2018
DOI: 10.1007/978-3-030-02131-3_20
|View full text |Cite
|
Sign up to set email alerts
|

What is a Minimum Viable (Video) Game?

Abstract: The concept of 'Minimum Viable Product' (MVP) is largely adapted in the software industry as well as in academia. Minimum viable products are used to test hypotheses regarding the target audience, save resources from unnecessary development work and guide a company towards a stable business model. As the game industry is becoming an important business domain, it is not surprise that the concept has been adopted also in the game development. This study surveys how a Minimum Viable Game (MVG) is defined, what is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Studies [37,38,39] have highlighted that prototypes could be used as MVPs since a prototype needs to be developed with 30 minimum effort to meet the business objectives and can be used by the internal team members for testing the product. The same prototype can also act as an MVP for demonstration to the customer or user to accumulate the validated learning.…”
Section: Mvp Development In Software Startupsmentioning
confidence: 99%
“…Studies [37,38,39] have highlighted that prototypes could be used as MVPs since a prototype needs to be developed with 30 minimum effort to meet the business objectives and can be used by the internal team members for testing the product. The same prototype can also act as an MVP for demonstration to the customer or user to accumulate the validated learning.…”
Section: Mvp Development In Software Startupsmentioning
confidence: 99%
“…They identified goals, challenges, and practices common to these companies and mapped them into the stages. Hyrynsalmi et al [13] used a subset of nine answers to understand how game developing startups are applying the Minimum Viable Product (MVP) concept. The results showed that the views on the topic are divergent and practical guidelines were still lacking.…”
Section: Resultsmentioning
confidence: 99%
“…The most common type of research approach described as a case survey was a method based on primary, but limited, data from a large number of instances of the phenomenon under study that the authors called "cases. " Data consisted of answers to a questionnaire (in the case of the startup studies that used the same data to study different aspects of these companies [13,17,18,37]) or online resources, i.e., blog posts, to investigate software startup pivots [1].…”
Section: Discussionmentioning
confidence: 99%
“…Being rather simple in terms of game play and short in terms of game length—the experience they offer aims to be simple and easy to understand, while still perceived as entertaining—when compared to games of other genres, casual games take a considerably lower amount of time to be designed, developed, and presented to consumers, which allows for thinner budgets without sacrificing game or aesthetic design quality [ 43 ]. This answers the premise of the minimum viable product (MVP), which refers to a product version that is used to collect validated learning from potential customers and users with the minimum amount of development effort, therefore saving time and cost resources [ 44 ].…”
Section: Discussionmentioning
confidence: 99%